Mourning headband for Hue : an account of the battle for Hue, Vietnam 1968 - Nhã Ca, 1939- (Indiana University Press, 2014)
"Vietnam, January, 1968. As the citizens of Hue are preparing to celebrate Tet, the start of the Lunar New Year, Nhã Ca arrives in the city to attend her father's funeral. Without warning, war erupts all around them, drastically changing or cutting short their lives. After a month of fighting, their beautiful city lies in ruins and thousands of people are dead. Mourning Headband for Hue tells the story of what happened during the fierce North Vietnamese offensive and is an unvarnished and riveting account of war as experienced by ordinary people caught up in the violence"--